2021
DOI: 10.1371/journal.pone.0249225
|View full text |Cite
|
Sign up to set email alerts
|

Case fatality and recurrent tuberculosis among patients managed in the private sector: A cohort study in Patna, India

Abstract: Background A key component of the WHO End TB Strategy is quality of care, for which case fatality is a critical marker. Half of India’s nearly 3 million TB patients are treated in the highly unregulated private sector, yet little is known about the outcomes of these patients. Using a retrospective cohort design, we estimated the case fatality ratio (CFR) and rate of recurrent TB among patients managed in the private healthcare sector in Patna, India. Methods World Health Partners’ Private Provider Interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The RTB observed in the current survey is high, in terms of absolute numbers, for a country like India. The proportion of RTB patients identified in the survey is slightly higher than proportion of sputum smear positive retreatment patients (24%) as reported in the NTEP [ 8 ] This is higher than the reported proportion of relapse in Zambia and other African counties [ 9 ]. of TB indicate that patients were cured but the underlying medical or social conditions have not been addressed completely.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The RTB observed in the current survey is high, in terms of absolute numbers, for a country like India. The proportion of RTB patients identified in the survey is slightly higher than proportion of sputum smear positive retreatment patients (24%) as reported in the NTEP [ 8 ] This is higher than the reported proportion of relapse in Zambia and other African counties [ 9 ]. of TB indicate that patients were cured but the underlying medical or social conditions have not been addressed completely.…”
Section: Discussionmentioning
confidence: 63%
“…proportion of sputum smear positive retreatment patients (24%) as reported in the NTEP [8] This is higher than the reported proportion of relapse in Zambia and other African counties [9]. of TB indicate that patients were cured but the underlying medical or social conditions have not been addressed completely.…”
Section: Plos Onementioning
confidence: 71%
“…Across 51 studies reporting adjusted analyses including people with drug-susceptible TB, indicators of diagnostic delay or advanced TB—including illness >2 months in 1 study [ 102 ], advanced radiographic (e.g., cavitary) disease in 2 studies [ 102 , 103 ], and smear–positive or microbiologically diagnosed TB (versus smear–negative, extrapulmonary, or clinically diagnosed TB) in 11 studies [ 68 , 70 , 71 , 73 , 76 , 81 , 85 , 87 , 89 , 97 , 104 ]—were associated with unfavorable treatment outcomes (Fig J in the S6 Appendix and Table D in the S4 Appendix ). People with more severe symptoms at treatment initiation were less likely to experience loss to follow-up in 2 studies [ 91 , 105 ], but more likely to experience composite unfavorable TB treatment outcomes in 1 study [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“… All studies used multivariable regression and reported adjusted effect estimates [ 66 , 67 , 71 73 , 77 , 81 , 84 , 86 , 87 , 89 94 , 99 – 105 , 108 110 , 123 ]. Estimates greater than 1 represent increased risk of unfavorable outcomes; estimates less than 1 represent decreased risk of unfavorable outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation